Rare DCM associated variants in pre-miR-208a disrupt miRNA maturation and function - Reckman, Yolan J.; Haas, Jan; van der Made, Ingeborg; Williams, Simon G.; Diaz, Iria Gomez; Akhtar, Mohammed; Mogensen, Jens; Rasmussen, Torsten B; Villard, Eric; Charron, Philippe; Elliott, Perry; Keavney, Bernard D; et al. (Human molecular genetics, 2025)
Dilated cardiomyopathy (DCM) is a major cause of heart failure (HF) defined by ventricular dilatation and systolic dysfunction. Although microRNAs (miRNAs) are known to affect HF development, little is known about the contribution of genetic variants in miRNAs or their precursors to the susceptibility or pathogenesis of DCM. We screened 1640 DCM cases for variants in cardiac miR-208a and miR-208b and their precursors. We identified four variants in the miR-208a pre-miRNA, which are present at very low frequencies in the general population. Two of these variants (+42G > T and +68G > T) alter a highly conserved nucleotide and the predicted pre-miRNA secondary structure. Both variants result in reduced mature miR-208a levels in overexpression experiments. The variant +42G > T also increased pre-miR-208a levels in these experiments, which indicates a maturation deficiency. Co-transfection of the overexpression constructs with a luciferase construct containing six miRNA binding sites revealed that both variants also impair repression of luciferase expression by miR-208a, indicative of also a loss of miR208a function. Together this indicates that these DCM-associated variants impair formation of mature miR208a. Combined with the role of miR-208a in cardiac contractility this suggests that variants +42G > T and +68G > T in pre-miR-208a may contribute to the DCM phenotype observed in these patients.